Relationship of Inflammatory Biomarkers with Severity of Peripheral Arterial Disease - Kimihiro Igari; Toshifumi Kudo; Takahiro Toyofuku; Yoshinori Inoue (International Journal of Vascular Medicine)
Objective. The pentraxin family, including high-sensitivity C-reactive protein (hs-CRP), serum amyloid P (SAP), and pentraxin 3 (PTX3), has been identified as playing a key role in inflammatory reactions such as in atherosclerosis and cardiovascular disease. In this study, we examined the relationship between peripheral arterial disease (PAD) and serum levels of pentraxins. Methods. This study was undertaken via a retrospective review of PAD patients with surgical intervention for lesions of the common femoral artery. We evaluated the preoperative patient conditions, hemodynamic status, such as ankle brachial index (ABI), and clinical ischemic conditions according to Rutherford classification. Preoperatively, we collected blood samples for determining the serum levels of hs-CRP, SAP, and PTX3. Results. Twelve PAD patients with common femoral arterial lesions were treated and examined. The hemodynamic severity of PAD was not negatively correlated with hs-CRP, SAP, or PTX3. The clinical severity evaluated by Rutherford classification was significantly positively correlated with the serum level of PTX3 (p=0.019). Conclusion. We demonstrated that PTX3 might be a better marker of PAD than hs-CRP and SAP. Furthermore, PTX3 might be a prognostic marker to evaluate the severity of PAD.